Bioinorganic Nanoparticles for the Remediation of Environmental Pollution: Critical Appraisal and Potential Avenues - Md. Mominur Rahman; Limon Ahmed; Fazilatunnesa Anika; Anha Akter Riya; Sumaiya Khatun Kali; Abdur Rauf; Rohit Sharma (Bioinorganic Chemistry and Applications)
Nowadays, environmental pollution has become a critical issue for both developed and developing countries. Because of excessive industrialization, burning of fossil fuels, mining and exploration, extensive agricultural activities, and plastics, the environment is being contaminated rapidly through soil, air, and water. There are a variety of approaches for treating environmental toxins, but each has its own set of restrictions. As a result, various therapies are accessible, and approaches that are effective, long-lasting, less harmful, and have a superior outcome are extensively demanded. Modern research advances focus more on polymer-based nanoparticles, which are frequently used in drug design, drug delivery systems, environmental remediation, power storage, transformations, and other fields. Bioinorganic nanomaterials could be a better candidate to control contaminants in the environment. In this article, we focused on their synthesis, characterization, photocatalytic process, and contributions to environmental remediation against numerous ecological hazards. In this review article, we also tried to explore their recent advancements and futuristic contributions to control and prevent various pollutants in the environment.